Pengajaran tentang Roh Kudus bagi Pembinaan Warga Jemaat Dewasa di Gereja Berdasarkan Surat Efesus - Deiby Ketlin Najoan (Sekolah Tinggi Teologi Kalimantan, 2021)
Teaching about the Holy Spirit is an important theme in the teaching curriculum for the formation of adult members of the church. Paul's letter to the Ephesians emphasized the importance of living under the leading of the Holy Spirit. The church must carry out the teaching of the Holy Spirit in the formation of the members of the congregation, so that the congregation has a correct understanding. Through a literature study approach related to the study of the Ephesians, it was found that the teaching of the Holy Spirit in Ephesians is the Holy Spirit as a seal, believers are sealed with the Holy Spirit when they believe which signifies that believers belong to God. The Holy Spirit is the guarantee that believers will receive what He has promised. Believers are the abode of the Holy Spirit, because the Holy Spirit indwells believers. The Holy Spirit empowers believers by His Spirit within. Believers should not grieve the Holy Spirit, but believers are commanded to be continually filled with the Holy Spirit. It is the Holy Spirit who guides believers in prayer. The Bible study in Ephesians about the Holy Spirit can be a reference for the church to implement a curriculum for teaching about the Holy Spirit for the formation of adult members of the congregation. The teachings of the Bible in the letter of Ephesians are the basis for the importance of teaching the Holy Spirit to adult members of the church.Pengajaran mengenai Roh Kudus merupakan tema penting dalam kurikulum pengajaran bagi pembinaan warga jemaat dewasa di gereja. Surat Paulus kepada jemaat di Efesus menekankan pentingnya hidup dalam pimpinan Roh Kudus. Gereja harus melaksanakan pengajaran mengenai Roh Kudus dalam pembinaan warga jemaat, supaya jemaat memiliki pemahaman yang benar. Melalui pendekatan studi literatur terkait dengan kajian surat Efesus, ditemukan bahwa pengajaran Roh Kudus dalam surat Efesus ialah Roh Kudus sebagai meterai, orang percaya dimeteraikan dengan Roh Kudus sewaktu percaya yang menandakan bahwa orang percaya adalah milik Allah. Roh Kudus menjadi jaminan bahwa orang percaya akan menerima apa yang telah dijanjikan-Nya. Orang percaya adalah tempat kediaman Roh Kudus, karena Roh Kudus yang mendiami orang percaya. Roh Kudus memberi kekuatan kepada orang percaya oleh Roh-Nya di dalam batin. Orang percaya tidak boleh mendukakan Roh Kudus, melainkan orang percaya diperintahkan untuk terus menerus dipenuhi oleh Roh Kudus. Roh Kuduslah yang menuntun orang percaya dalam berdoa. Kajian Alkitab dalam surat Efesus mengenai Roh Kudus dapat menjadi acuan bagi gereja untuk pelaksanaan kurikulum pengajaran tentang Roh Kudus bagi pembinaan warga jemaat dewasa. Ajaran alkitab dalam surat Efesus menjadi landasan tentang pentingnya pengajaran Roh Kudus bagi jemaat dewasa di gereja.